2022
DOI: 10.3847/1538-4357/ac35ec
|View full text |Cite
|
Sign up to set email alerts
|

An Early-time Optical and Ultraviolet Excess in the Type-Ic SN 2020oi

Abstract: We present photometric and spectroscopic observations of Supernova 2020oi (SN 2020oi), a nearby (∼17 Mpc) type-Ic supernova (SN Ic) within the grand-design spiral M100. We undertake a comprehensive analysis to characterize the evolution of SN 2020oi and constrain its progenitor system. We detect flux in excess of the fireball rise model δ t ≈ 2.5 days from the date of explosion in multiband optical and UV photometry from the Las Cumbres Observatory and the Neil Gehrels Swift Observatory, resp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 190 publications
0
35
0
Order By: Relevance
“…SN 2022oqm shows several peculiarities separating it from the general SN Ic population. It has an early peak only seen in several other SNe Ic-BL and SNe Ic, a C/O CSM, directly observed so far only in rare cases such as SNe Icn (e.g., Ben-Ami et al 2014;Gal-Yam et al 2022;Perley et al 2022;Gagliano et al 2022;Pellegrino et al 2022), and indirectly implied for SN 2018gep through its precursor emission (Ho et al 2019). Its Ca-rich nebular spectrum, peak luminosity at 12 days and offset loca-tion are consistent with the Ca-rich population (Perets et al 2010;Kasliwal et al 2012;De et al 2018).…”
Section: A Population Of Explosions?mentioning
confidence: 99%
See 1 more Smart Citation
“…SN 2022oqm shows several peculiarities separating it from the general SN Ic population. It has an early peak only seen in several other SNe Ic-BL and SNe Ic, a C/O CSM, directly observed so far only in rare cases such as SNe Icn (e.g., Ben-Ami et al 2014;Gal-Yam et al 2022;Perley et al 2022;Gagliano et al 2022;Pellegrino et al 2022), and indirectly implied for SN 2018gep through its precursor emission (Ho et al 2019). Its Ca-rich nebular spectrum, peak luminosity at 12 days and offset loca-tion are consistent with the Ca-rich population (Perets et al 2010;Kasliwal et al 2012;De et al 2018).…”
Section: A Population Of Explosions?mentioning
confidence: 99%
“…Occasionally, a coincident gammaray burst (GRB) or X-ray flash (XRF) resulted in intense UV-optical follow-up observations (Campana et al 2006;Soderberg et al 2008). Several other well-studied normal and peculiar SNe Ic (De et al 2018;Horesh et al 2020), broad-lined SNe Ic (Ic-BL; reported by Ho et al 2019Ho et al , 2020a, and SNe Icn (Gal-Yam et al 2022;Perley et al 2022;Pellegrino et al 2022;Gagliano et al 2022) have been found, showing diverse properties. In some of these cases, a short-lived early blue peak has been observed, possibly consistent with the shock cooling of a low-mass envelope, shock-breakout from a confined shell of CSM, or the subsequent cooling of the shocked material.…”
Section: Introductionmentioning
confidence: 97%
“…In the context of SN Ia correlation between the observed luminosity at the maximum light to the 56 Ni see (Stritzinger et al 2006). (Arnett 1982;Stritzinger et al 2006;Gagliano et al 2022). 𝛾-rays released in this process are then thermalized in the expanding SN ejecta and, for phases 𝑡 60 days after explosion, 56 Co beta-decay will power the bolometric light curve until the decays of other radioactive species such as 57 Co and 55 Fe become dominant (e.g., 𝑡 50 days after explosion; red dot-dashed line in Fig.…”
Section: Radioactive Decay + Ni Mass Modelmentioning
confidence: 99%
“…where 𝑡 Ni = 8.77 days, 𝑡 Co = 111.3 days is the timescale for the radioactive decay of 56 Ni into 56 Co and 56 Co into 56 Fe, and 𝜀 Ni = 3.9×10 10 erg g −1 s −1 and 𝜀 Co = 6.8×10 9 erg g −1 s −1 are the specific heating rates (the amount of energy per unit mass released) from these decays (in solar mass units: 𝜀 Ni = 6.45 × 10 43 erg s −1 M −1 and 𝜀 Co = 1.45 × 10 43 erg s −1 M −1 ). We adopt a value of 𝛽 = 0.9, suitable for SNe Ic (Gagliano et al 2022). The diffusion timescale 𝑡 𝑑 can be calculated from the rise time 𝑡 𝑠 by numerically solving the equation…”
Section: Radioactive Decay + Ni Mass Modelmentioning
confidence: 99%
See 1 more Smart Citation